math

(3x2(3)/11-5(5))^2

  1. 👍 0
  2. 👎 0
  3. 👁 101
  1. (3X^2 * (3)/11 - 5*5^2.
    Common denominator = 11:

    (3X^2*(3)-55*25) / 11=(9X^2-1375)/11.

    1. 👍 0
    2. 👎 0

Respond to this Question

First Name

Your Response

Similar Questions

  1. Math

    Q.1)If one zero of the polynomial 3x2-kx-2 is 2 find the other zero.allso find the value of k. Q.2)If sum of the zeroes of the polynomial x2-x-k(2x-1) is 0,find the value of k Q.3)If 2 and 3 are the zeroes of the polynomial

    asked by stan on April 24, 2010
  2. Algebra

    Can you please help me with this problem? (8X2^Y0^Z6^)2^ + 3X2^ + z12^ + 5Y0^z12^ 64X4^Y2^Z8^ + 3X2^ + Z12^ + 5Y0^Z12^ 67X6^ + 5Y2^ + Z32^

    asked by Lucille on January 30, 2017
  3. Algebra

    When 3x2 – 2x + 1 is subtracted from 2x2 + 7x + 5, the result will be what? do I subtract 3x2 – 2x + 1 - 2x2 + 7x + 5 like this or 2x2 + 7x + 5 - 3x2 – 2x + 1 like this?

    asked by Anonymous on February 10, 2016
  4. Math

    3x² - 4 = 23

    asked by Tracey on October 6, 2011
  5. further math

    identify the conic sections below (circle,hyperbola,parabola,ellipse). a)3x2+3y2-2y=4 b)3x2-9y2+2x-4y=7 c)2x2+5y2-7x+3y-4=0 d)3y2-4x+17y=-10

    asked by fiyin on June 4, 2017
  1. Integrated Math 1

    The parabolas y = -3x2 + 10x - 6 and y = -3x2 - 17x + 2 intersect at _____? A.the line y = 27x - 8. B. x=the square root of 2 over 3 and xthe -square root of 2 over 3. C. x=8/27. D. they do not intersect.

    asked by Tifini on July 8, 2012
  2. algebra

    The expression 3x² represents

    asked by kelcie on November 17, 2014
  3. Algebra

    Write an expression that is equal to 3x2 1/4

    asked by Isabella on January 14, 2017
  4. math

    Evaluate the polynomial for x = -2. Simplify your answer 3x² - 2x +2

    asked by Mary on April 24, 2011
  5. calculus

    to find value of x and discontinous 9x²-3x-2/3x²+13x-4

    asked by Nico on September 17, 2013
  6. algebra

    Can someone please explain What polynomial has a graph that passes through the given points? (–4, 89), (–3, 7), (–1, –1), (1, –1), (4, 329) y = 2x3 – 3x2 – 2x + 1 y = 1x4 – 2x3 – 3x2 + 2x + 1 y = x4 – 2x3 + 3x2

    asked by lee on November 14, 2012

You can view more similar questions or ask a new question.